2018
DOI: 10.1016/j.neuro.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of 1,2-propanediol in zebrafish (Danio rerio)

Abstract: The use of electronic cigarettes (e-cigarettes) is increasing despite insufficient information concerning their long-term effects, including the effects of maternal e-cigarette use on pre- and postnatal development. Our previous study demonstrated that developmental exposure to 1,2-propanediol (a principal component of e-cigarette liquid) affected early development of zebrafish, causing reduced growth, deformities, and hyperactive swimming behavior in larvae. The current study extends assessment of the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Massarsky et al evaluated the neurobehavioral impact of 1,2-PDO toxicity in a zebrafish model, assessing two different concentrations (0.625% and 1.25%). In this study, 1,2-PDO was associated to a hyperactive swimming pattern, concluding that these substances may cause long-term neurobehavioral consequences [72].…”
Section: Electronic Nicotine Delivery Systems (Ends)supporting
confidence: 52%
“…Massarsky et al evaluated the neurobehavioral impact of 1,2-PDO toxicity in a zebrafish model, assessing two different concentrations (0.625% and 1.25%). In this study, 1,2-PDO was associated to a hyperactive swimming pattern, concluding that these substances may cause long-term neurobehavioral consequences [72].…”
Section: Electronic Nicotine Delivery Systems (Ends)supporting
confidence: 52%
“…In vitro, aerosols from glycerol only-containing refills showed cytotoxicity in A549 and human embryonic stem cells, even at a low battery output voltage [ 59 ]. PG was also found to affect early neurodevelopment in a zebrafish model [ 60 ]. Another important issue is that, under heating conditions PG can produce acetaldehyde or formaldehyde (119.2 or 143.7 ng/puff at 20 W, respectively, on average), while glycerol can also generate acrolein (53.0, 1000.0 or 5.9 ng/puff at 20 W, respectively, on average), all carbonyls with a well-documented toxicity [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, animals exposed to hazardous chemicals can change their behavior and these changes may affect their survival, growth, and reproduction (Wang et al, 2018). Previous study has been reported that embryonic exposure to PG can result in behavioral changes in zebra sh larvae (Massarsky et al, 2018). In the present study, we found that embryonic exposure to R-, S-, and RS-PG of high doses could signi cantly induce the locomotor hyperactivity of zebra sh larvae, demonstrating that R-, S-, and RS-PG of high doses could cause the neurodevelopmental effect in zebra sh larvae.…”
Section: Discussionmentioning
confidence: 99%
“…PG has very low toxicity and is considered to be a non-toxic or non-carcinogenic compound for adults (Zaripov et al, 2020). However, newborns and infants are specially susceptible to the effects of PG (Massarsky et al, 2018). In the present study, our results showed that R-, S-, and RS-PG enantiomers of high doses can exhibit the neurotoxicity and ocular developmental toxicity in zebra sh larvae, indicating that R-, S-, and RS-PG exposures of high doses have the potential neurotoxicity and ocular developmental toxicity for infants and toddlers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation